How Does Industry Structure Affect Upside Cost Stickiness? An Explanation for IT Industry - Jin, Byunghoon (Journal of Accounting, Business and Management (JABM), 2025)
While prior literature on the asymmetric behavior of costs has predominantly focused on firms experiencing losses, a number of recent studies have shifted the focus to the opposite side, documenting that firms tend to hesitate to incur additional costs (i.e., make additional investments in resources) when faced with an unusually large increase in sales revenue. To extend the existing literature on this “upside cost stickiness,” this study examines how the asymmetric cost behavior of firms with an unusually large sales increase is influenced by factors such as industry characteristics and a firm’s position within the industry. Drawing on economic theory regarding the relationship between industry structure and corporate behavior, this research predicts that the degree of upside cost stickiness is weaker for industry leaders and diminishes as market concentration increases. As an application, this study further predicts that upside cost stickiness is weaker for firms in the concentrated IT industry. These predictions are strongly supported by empirical evidence based on 135,649 unique firm-year observations.